Melanogenesis-Inhibitory and Cytotoxic Activities of Chemical Constituents from the Leaves of Sauropus androgynus L. Merr. (Euphorbiaceae) - Jie Zhang (2018)
© 2018 Wiley-VHCA AG, Zurich, Switzerland A new steroid, 20-hydroxyisofucosterol (stigmasta-5,24(28)-diene-3β,20β-diol) (7), along with six known compounds 1 – 6 were isolated from the MeOH extract of the leaves of Sauropus androgynus L. Merr. (Euphorbiaceae). The structure of new steroid was determined by HR-APCI-MS and various NMR techniques in combination with literature data. Subsequently, their anti-inflammatory, cytotoxic activities against five human cell lines, as well as inhibitory activities against the α-MSH induced melanogenesis on the B16 cell line were evaluated. As the results, steroid compounds, 6 and 7 exhibited moderate cytotoxic to HL60, AZ521, SKBR3, and A549 tumor cell lines (IC5026.9 – 45.1 μm) with high tumor selectivity for A549 relative to WI38 cell lines (SI 2.6 and 3.0, resp.). And, flavonoid compounds, 4 and 5 exhibited superior inhibitory activities against melanogenesis (67.0 – 94.7% melanin content), even with no or low toxicity to the cells (90.1 – 99.6% cell viability) at the concentrations from 10 to 100 μm. Furthermore, Western blot analysis suggested that compound 5 could inhibit melanogenesis by suppressing the protein expressions of MITF, TRP-1, TRP-2, and tyrosinase.